Perceptual Hashing-Based Robust Image Authentication Scheme for Wireless Multimedia Sensor Networks - Hongxia Wang; Bangxu Yin (International Journal of Distributed Sensor Networks)
Image authentication is critical for secure image transmission and storage in a wireless multimedia sensor network (WMSN). In this paper, we propose a perceptual hashing-based robust image authentication scheme, which applies the distributed processing strategy for perceptual image hashes and can provide compactness, visual fragility, perceptual robustness, and security in digital image authentication for WMSN. In the proposed scheme, first, the cluster head node generates a secure pseudorandom chaotic sequence with keys and sends it to the image capturing node, then the image capturing node uses the received chaotic sequence to divide randomly the captured image into several overlapping rectangles, after that, two gravity centers of each rectangular region block are calculated, and finally the binary distance of the two gravity centers will be calculated in each general cluster member node. The cluster head node receives the binary sequence of the distance from all of the general cluster member nodes and combines them to form the perceptual hashing sequence to be sent to the base station for image authentication purpose. Experimental results show that the proposed scheme has satisfactory authentication ability and can ensure not only the visual fragility for perceptually distinct images but also robustness for perceptually identical images via image rotation, JPEG compression, and noise burring.